Small-scale high-cycle fatigue testing by dynamic microcantilever bending. (June 2020) - Gabel, Stefan; Merle, Benoit
Abstract : Abstract: The lifetime of cyclically loaded devices is often limited by the fatigue resistance of their individual phases. An advanced method is presented for measuring the high-cycle fatigue behavior of materials at the micrometer scale using a nanoindenter. It is based on the cyclic deflection of focused ion beam-fabricated microcantilevers using the continuous stiffness method (CSM). In line with experimental data on bulk nanocrystalline copper, the specimens exhibit grain coarsening followed by the formation of extrusions and a fatigue strength exponent of −0.10. The method is suitable for characterizing single phases and individual components of further complex systems.